2020
DOI: 10.1177/1948550620920982
|View full text |Cite
|
Sign up to set email alerts
|

Do Animals’ Minds Matter Less, When Meat Gets Personal? Replications of Piazza and Loughnan (2016) in China

Abstract: Piazza and Loughnan found that the high intelligence information about animals leads to higher moral standing judgment except for self-relevant animals. We replicated the original three studies in China. Study 1 finds that the intelligence information about a fictional animal does not affect moral standing judgment or hunting decisions, inconsistent with the original study. By manipulating the intelligence of animals in one’s culture (pig) versus in other cultures (tapir or trablan), Study 2 consistently finds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Research shows, for example, that ambivalence towards meat is experienced not only in Western countries but also by people from Argentina and Brazil (Ruby et al, 2016). In a similar vein, dissonance aroused by meat consumption is experienced and leads to similar downstream consequences in people from Ecuador, China, Singapore, or India like in THE MODEL OF AMBIVALENT CHOICE AND DISSONANT COMMITMENT 37 people from the global north (Ang et al, 2019;Khara et al, 2021;Kunst & Palacios Haugestad, 2018;Tian et al, 2016Tian et al, , 2020). Yet, this research also identifies boundary conditions for the experience and effects of conflict: For instance, conflicts that are aroused by associating meat with their animal origin are more pronounced in cultures that are less exposed to unprocessed meat (Kunst & Palacios Haugestad, 2018).…”
Section: Constraints On Generality and Citationsmentioning
confidence: 99%
“…Research shows, for example, that ambivalence towards meat is experienced not only in Western countries but also by people from Argentina and Brazil (Ruby et al, 2016). In a similar vein, dissonance aroused by meat consumption is experienced and leads to similar downstream consequences in people from Ecuador, China, Singapore, or India like in THE MODEL OF AMBIVALENT CHOICE AND DISSONANT COMMITMENT 37 people from the global north (Ang et al, 2019;Khara et al, 2021;Kunst & Palacios Haugestad, 2018;Tian et al, 2016Tian et al, , 2020). Yet, this research also identifies boundary conditions for the experience and effects of conflict: For instance, conflicts that are aroused by associating meat with their animal origin are more pronounced in cultures that are less exposed to unprocessed meat (Kunst & Palacios Haugestad, 2018).…”
Section: Constraints On Generality and Citationsmentioning
confidence: 99%
“…Moreover, Piazza and Loughnan (2016) showed that people's meat eating was associated with a reluctance to utilize information about food-animals' minds in moral judgement (see also Tian et al, 2021). In this work, participants were asked to consider an animal they eat (e.g., pigs) or an animal they do not eat (but that is eaten in other cultures; e.g., tapirs), as intelligent and inquisitive or lacking these traits.…”
Section: Motivated Perceptions Of Food-animal Mindsmentioning
confidence: 99%